Investigation on the regulatory roles of a second messenger cyclic diadenosine-monophosphate (C-DI-AMP) in streptococcus gallolyticus subsp. gallolyticus - Teh, Wooi Keong (Nanyang Technological University, 2019)
Streptococcus gallolyticus subsp. gallolyticus is an emerging pathogen responsible for infective endocarditis especially in the elderly. Many infected patients were found to exhibit a condition of concomitant colorectal neoplasia; therefore colonoscopy is now advised for S. gallolyticus-infected patients to screen for the presence of early stage colorectal tumours. It has been recently proposed that S. gallolyticus subsp. gallolyticus plays an auxiliary role in colorectal cancer development, albeit the detailed mechanisms allowing S. gallolyticus subsp. gallolyticus to promote the tumorous cells progression remains unidentified. Previous studies suggested that bacterial biofilms residing in the gastrointestinal tract may play a role in the colorectal cancer development. In this dissertation, the primary objective was to understand S. gallolyticus subsp. gallolyticus biofilm biology, for the interest of further investigations on the roles of S. gallolyticus subsp. gallolyticus biofilms in colorectal cancer development. I first provide evidence that S. gallolyticus subsp. gallolyticus biofilm development is controlled by the bacterial second messenger cyclic diadenosine-monophosphate (c-di-AMP). It was found that the deletion mutant (∆gdpP) of the c-di-AMP specific phosphodiesterase GdpP accumulating higher intracellular level of c-di-AMP displayed defect in biofilm development. Further investigations focusing on the molecular mechanisms of c-di-AMP control on S. gallolyticus subsp. gallolyticus biofilm development revealed that the expression of the extracellular pullulanase PulA and the extracellular appendage pili Pil3 is responsive to the intracellular c-di-AMP level. Both the reduced expression of PulA and Pil3 contribute in part to biofilm developmental defect of the S. gallolyticus subsp. gallolyticus ∆gdpP mutant. In view of the numerous studies that have indicated c-di-AMP to play a primary role in controlling bacterial osmotic homeostasis, the S. gallolyticus subsp. gallolyticus ∆gdpP mutant was characterised. It was found that the mutant cells were more sensitive to high osmotic stress and were smaller in cell size compared to the parental strain. It was also found that the expression of various transporters involved in controlling the uptake of osmolytes was down-regulated in the ∆gdpP mutant compared with the parental strain. Collectively, the present PhD thesis supports the notion that c-di-AMP plays a conserved role in maintaining osmotic homeostasis in many Gram-positive bacteria and establishes that c-di-AMP is a bona fide signalling molecule controlling S. gallolyticus subsp. gallolyticus biofilm development.